AB0901 Vaspin and lipocalin2 levels in psoriatic arthritis. (12th June 2018) - Colak, S.; Omma, A.; Can Sandikci, S.; Yucel, C.; Turhan, T.
Abstract : Background: Psoriathic athritis (PsA) is a type of spondiloarthropaties which is affiliated with psoriasis. Metabolic syndrome, diabetes mellitus and cardiovascular diseases are comorbid conditions associated with psoriatic arthritis. Adipokines are suggested to be playing proinflammatory or antiinflammatory roles in the proceeding of inflammatory situations. Objectives: The aim of this study is to investigate the recently interested adipokines vaspin and lipocalin2 levels and their association with disease activity of patients diagnosed with psoriatic arthritis. Methods: The study was conducted between October 2017 and January 2018 at the Rheumatology Clinic of Ankara Numune Training and Research Hospital, Turkey. The vaspin and lipocalin2 levels of 50 PsA patients, diagnosed according to the Classification Criteria for Psoriatic Arthrtis (CASPAR), and 36 age-and sex-matched healthy subjects were analysed in current study. The disease activity was assessed by using Psoriasis Area Severity Index, Bath Ankylosing Spondylitis Functional Index, Bath Ankylosing Spondylitis Disease Activity Index and Disease Activity Index for Psoriatic Arthritis. Indexes were applied to the patients in order to evaluate the disease activity. Results: No significant difference was found between groups with respect to age, sex and body mass index. There was significant difference between vaspin (p=0.001) and lipocalin2 (p=0.014) levels among the PsA patients and control groups. There was no significant difference between the groups in terms of disease activity (p>0.05). Conclusions: The results of this study points out the possible role of vaspin and lipocalin2 in PsA. In our knowledge, this is the first study comparing the vaspin and lipocalin2 levels of patients with PsA to healthy subjects and these findings may pioneer further studies investigating the usage of adipokines such as vaspin and lipocalin2 levels as biomarkers in the diagnose and disease course of PsA. Disclosure of Interest: None declared